537 Consensus driven design of child restraint product information to reduce misuse. (1st September 2016) - Hall, Alexandra; Ho, Catherine; Keay, Lisa; McCaffery, Kirsten; Hunter, Kate; Charlton, Judith; Bilston, Lynne; Hayen, Andrew; Brown, Julie
Abstract : Background: Correct use of an age-appropriate restraint reduces the risk of death and injury among child passengers. While rates of age-appropriate restraint continue to rise in most developed countries, misuse of restraints remains a significant problem. Measures that target the individual are effective in reducing misuse. Carers identify instructions supplied by manufacturers as a common source of information yet there is no evidence base for developing effective instructions for targeting misuse. We aim to develop enhanced product information for child restraints through expert consensus supplemented by consumer input and testing. Methods: A modified consensus method will be used. The consensus panel consists of experts in child safety and health literacy and industry professionals. A report synthesising health literacy, and human factors design principles combined with qualitative results from consumer focus groups will be used to construct a prototype of product information ( Round 1 ). This prototype will be sent to panel members for review and results are synthesised ( Round 2 ). The results are redistributed and panel members re-rank preferences in light of results ( Round 3 ). Round three is repeated until consensus is reached, at which stage the prototype is finalised and tested using consumer installation and comprehension trials ( Consumer input ). Consumer feedback will inform the next consensus cycle. Results: The final enhanced product information will be presented at the conference with an evaluation of the modified consensus method in developing safety information for preventing misuse. Conclusions: Child restraint product information is perhaps the most widely used and underutilised channel of communication for the correct use of child restraints. Product information that is developed using a consensus method involving consumers, child safety experts and industry professionals will ensure that the information is targeted and effective at preventing misuse.